(untitled) (Journal of Music Research Online, 2022)
We take stock of engagements occurring between music and environment and what this heralds for current and future music making and musicology. We consider five contemporary and emerging fields of interest that variously connect the two keywords: 1) music as commemoration or evocation of place; 2) soundscape studies and sound art; 3) acoustic ecology, ecomusicology, and environmental activism; 4) environmental ethnomusicology, archaeomusicology, zoömusicology, and biomusicology; and 5) music and its technological environment. Intersections of the two concepts are on the increase, particularly as composers, performers, and musicologists attempt to respond to matters of climate change, sustainability, and environmental collapse in novel and meaningful ways.